CFD analysis on hydrodynamic conditions of a designed spiral column photobioreactor for cultivation of microalgae. (2nd October 2017) - Chatterjee, Sushovan
Abstract : Purpose: The purpose of this study is analysis on fluid flow characteristics inside a modified designed spiral bubble column photo-bioreactor. Available fluid dynamic simulation of bubble column reactor (BCR) (which is well-known conventional photobioreactor) had shown significance contribution over the past two decades, where the fluid dynamics of the culture medium and mixing will influence the average irradiance and the light regimen to which the cells are exposed. This enhances the growth. To develop this, and also to cut down the cost parameter involving the production of biodiesel from algae, the growth rate of algae has to be enhanced. Design/methodology/approach: Some design modification through a staggered spiral-path inside the bubble column design had been proposed and comparative simulation of the modified design has been reported. Three-dimensional simulations of gas–liquid flow both in the BCR and spiral path column reactor have been carried out using the Euler–Euler approach. Various graphs are plotted, and from comparing, it has been seen that the proposed reactor will enhance better mixing rate, which could help the growth rate in microalgae in the present proposed model. In this paper, an earnest attempt had made to carry out computational simulation of conventional BCR and designed reactor used for cultivation of microalgae which had analyzed using commercial code ANSYS 14. Findings: From this work, it was observed that the average turbulence kinetic energy fluctuates more in designed reactor over the conventional photo bioreactor, which will in turn increase diffusivity and enhance transfer of mass, momentum and energy. The results provide comprehensive information concerning effect of fluid flow characteristics inside a modified designed spiral bubble-column photo-bioreactor. Originality/value: Some of our earlier published results (www.scientific.net/AMM.592-594.2427 ) are also referred in this paper. This work had been performed under the financial aid from RPS project (no. 8, 023/RID/RPS/27/11/12), sponsored by All India Council for Technical Education.